“Don’t think of a soda”: Contradictory public health messaging from a content analysis of Twitter posts about sugar-sweetened beverage taxes in California from 2015 to 2018 - Garcia, Kim; Mejia, Pamela; Perez-Sanz, Sarah; Dorfman, Lori; Madsen, Kristine; Schillinger, Dean (Frontiers in Public Health, 2024)
To show how sugar-sweetened beverage (SSB) taxes were framed in posts on Twitter (now known as X) through text and images, we conducted a content analysis on a sample of Tweets from California users posted between January 1, 2015 and December 31, 2018 about SSB taxes in Berkeley, San Francisco, Oakland, and/or Albany, California. We evaluated posts for information sources, arguments for or against SSB tax policies, and images used. We found that posts presented a mix of messages through text and images. The majority of posts (64%) included arguments supporting SSB taxes, 28% presented a neutral position (e.g., factual information) or a mix of both pro-and anti-tax arguments, and 8% opposed. One-third of posts included an image, almost half of which appeared to be stock photos from SSB advertisements: many of these were shared by medical and public health users. Some tax supporters also reposted messages and images from opposition campaigns and added their own criticisms. By reposting opponents’ anti-tax messages and images of SSBs, tax supporters may have inadvertently promoted SSBs, reinforced opposition to SSB taxes, and normalized SSBs. While advocates effectively shared pro-tax arguments, they should also ensure that accompanying images reflect the solutions they seek, not just the problem they are trying to combat.